1994
DOI: 10.1128/iai.62.7.2857-2864.1994
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences, immunoglobulin classes, and biological activities of antibodies in normal human serum that are reactive with Cryptococcus neoformans glucuronoxylomannan

Abstract: Serum obtained from normal human subjects contains antibodies reactive in an enzyme-linked immunosorbent assay with the glucuronoxylomannan (GXM) of Cryptococcus neoformans. The frequency of occurrence of class-specific antibodies among normal subjects was 28% for immunoglobulin G (IgG), 98% for IgM, and 3% for IgA. Anti-GXM antibodies with kappa light chains occurred in 98% of normal subjects, while the occurrence of lambda light chains was 28%. Each of five subjects with high levels of anti-GXM IgG antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 28 publications
3
43
0
3
Order By: Relevance
“…Previous study reported that humans have preexisting antibodies reactive with glucuronoxylomannan. [14][15][16][17] Three studies [7][8][9] reported preexisting antibodies in human against cryptococcal proteins. The findings provide indirect evidence of C. neoformans infections in immunocompetent individuals and support the concept that humans may have ongoing exposure to C. neoformans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that humans have preexisting antibodies reactive with glucuronoxylomannan. [14][15][16][17] Three studies [7][8][9] reported preexisting antibodies in human against cryptococcal proteins. The findings provide indirect evidence of C. neoformans infections in immunocompetent individuals and support the concept that humans may have ongoing exposure to C. neoformans.…”
Section: Discussionmentioning
confidence: 99%
“…Glucuronoxylomannan was isolated from the culture supernatant fluid of serotype A strain CN 6, as previously described (Houpt et al, 1994;Cherniak et al, 1980). Isolated soluble GXM contained < 125 pg LPS mg -1 of GXM as detected by Limulus amebocyte lysate assay (Sigma).…”
Section: Cryptococcal Polysaccharidementioning
confidence: 99%
“…To eliminate LPS contamination in the GalXM preparation, this polysaccharide was dialysed extensively versus LPS-free water and the dialysate changed until negative by Limulus amobocyte assay. GXM was obtained from TR Kozel (Department of Microbiology and Immunology, University of Nevada, Reno, NE) and was isolated and purified as described elsewhere (Cherniak et al, 1980;Houpt et al, 1994). Purified soluble GXM contained < 125 pg LPS/mg of GXM as detected by Limulus amebocytes lysate assay.…”
Section: Microorganisms and Cryptococcal Polysaccharidementioning
confidence: 99%